2018
DOI: 10.1136/tobaccocontrol-2018-054562
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe tobacco package warning exposure’s impact on risk perceptions and use among young adults in the USA: a longitudinal analysis of the population assessment of tobacco and health study

Abstract: More than one-third of US young adult current waterpipe users reported WTP warning exposure prior to FDA-mandated warning implementation. Findings suggest the mandated warning may result in high exposure among users; it will be critical to assess exposure's impact on risk perceptions and behaviour after FDA-mandated warnings are implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…A study conducted a year prior found that only 5.7% of adult participants reported noticing warnings on vaping devices (McDermott et al, 2019). In another study with youth in the US, 35.5% of current users reported exposure to warnings on shisha products prior to warning standardization (King et al, 2018), similar to rates among current e-cigarette users in this study. By comparison, studies that assessed noticing warnings on regulated products with mandated warnings revealed higher rates of exposure.…”
Section: Discussionsupporting
confidence: 83%
“…A study conducted a year prior found that only 5.7% of adult participants reported noticing warnings on vaping devices (McDermott et al, 2019). In another study with youth in the US, 35.5% of current users reported exposure to warnings on shisha products prior to warning standardization (King et al, 2018), similar to rates among current e-cigarette users in this study. By comparison, studies that assessed noticing warnings on regulated products with mandated warnings revealed higher rates of exposure.…”
Section: Discussionsupporting
confidence: 83%
“…The findings indicate that targeting beliefs on the harmfulness and addictiveness may influence the willingness to quit among users and desire to try among nonusers. Mandated waterpipe tobacco package warning may result an increase of awareness of the health effects of WTS (King et al, 2019), and thus increase in the level of risk perception (Salloum et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While, historically, most research on health warnings has focused on cigarettes, there is a growing need for evidence to support health warning implementation and content on non-cigarette tobacco products. King et al 6 examine the data from the first two waves of the Population Assessment of Tobacco and Health (PATH) study in the USA for self-reported exposure to manufacturer-implemented warnings on waterpipe tobacco products, prior to the August 2018 requirement to place a nicotine warning on waterpipe tobacco. About one-third of users reported seeing some type of warning, and this was associated with having regular brand and purchasing for self.…”
Section: Richard O'connormentioning
confidence: 99%